Behaviour analysis of STREE, SABR and SARDS under different simulation enviornements:A Case Study. (International Journal of Engineering and Computer Science, 2017)
The Wireless Sensor Network (WSN) has been continuous target for research because of Its potential use in data collection Techniques in different hostile and un secured environments. Various techniques and Methods has been explored by different researchers in the area of minimizing energy efficiency and maximizing security concerns in WSN, But still It is one of the key area to look further. In future WSN will be connected to Internet of Things (IoT) so researches need to study the behavior of proposed techniques in different simulation environments. In this paper we have case studied and shown the our earlier proposed Techniques i.e. STREE,SABR and behave in different simulation environments.